2020
DOI: 10.1136/jitc-2019-000169
|View full text |Cite
|
Sign up to set email alerts
|

Targeting ANXA1 abrogates Treg-mediated immune suppression in triple-negative breast cancer

Abstract: BackgroundRegulatory T (Treg) cells play a negative role in anti-tumor immunity against triple-negative breast cancer, so it is of great significance to find the potential therapeutic target of Treg cells.MethodsFirst, Annexin A1 (ANXA1) expression and survival of patients with breast cancer were analyzed using TCGA data. Then plasma ANXA1 levels in patients with malignant and benign breast tumors were detected by ELISA. Next, the effect of ANXA1 on Treg cells was studied through suppressive assays, and how AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 43 publications
2
61
0
Order By: Relevance
“…When implanted into Anxa1 null syngeneic mice, murine Lewis lung carcinoma (LLC) cells were shown to have a reduced growth rate and spontaneous metastasis to lung relative to wild-type mice [ 59 ]. Therefore, the growth rates of control and Annexin-A1-depleted EO771.LMB orthotopic allografts were assessed in wild-type mice as well as in syngeneic C57BL/6 mice null for either Anxa1, or its receptor on regulatory T cells, Fpr2 [ 26 ]. Stable Annexin A1 knockdown had no effect on the initiation or growth rates of EO771.LMB tumors in wild-type ( Figure S12B,E ), Anxa1 null ( Figure S12C ), or Fpr2 null ( Figure S12D ) mice, and had no effect on final tumor mass ( Figure S12F ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When implanted into Anxa1 null syngeneic mice, murine Lewis lung carcinoma (LLC) cells were shown to have a reduced growth rate and spontaneous metastasis to lung relative to wild-type mice [ 59 ]. Therefore, the growth rates of control and Annexin-A1-depleted EO771.LMB orthotopic allografts were assessed in wild-type mice as well as in syngeneic C57BL/6 mice null for either Anxa1, or its receptor on regulatory T cells, Fpr2 [ 26 ]. Stable Annexin A1 knockdown had no effect on the initiation or growth rates of EO771.LMB tumors in wild-type ( Figure S12B,E ), Anxa1 null ( Figure S12C ), or Fpr2 null ( Figure S12D ) mice, and had no effect on final tumor mass ( Figure S12F ).…”
Section: Resultsmentioning
confidence: 99%
“…Extracellular or membrane-associated, externally facing Annexin A1 synthesized by cancer cells has many possible functions in the tumor microenvironment. In addition to autocrine action, Annexin A1 can signal in a paracrine or juxtacrine mode to FPRs on tumor-infiltrating leukocytes, such as dendritic cells [ 22 ], tumor-associated macrophages [ 23 ], neutrophils [ 24 ], natural killer (NK) cells [ 25 ], or T cells [ 25 , 26 ], which could potentially influence immune cell function to favor tumor growth. For example, Annexin A1 released from tumor cells was shown recently to activate Fpr2 on the surface of regulatory T cells to enhance their immunosuppressive function [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the eight DEIGs, there are few studies in bladder cancer, but some of their interactions with immunity have been explored and verified in other researches. ANXA1 can enhance the function of regulatory T cells (Tregs) and reduce the survival rate of patients with breast cancer ( Bai et al, 2020 ). IL-22 producing T cells in colorectal cancer enhance T cell function by recruiting neutrophils, thereby enhancing immune response ( Tosti et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study using transgenic mice indicated that T cell-expressed ANXA1 functions to attenuate T cell-driven inflammatory responses via T cell-intrinsic effects on intracellular signaling, proliferation, and Th1/Th17 cytokine release 36 . Only a few studies have described ANXA1 expression in Treg cells 38 , 39 . These data indicated that ANXA1 could enhance the inhibitory function of Treg cells.…”
Section: Discussionmentioning
confidence: 99%